2014
DOI: 10.1523/jneurosci.5310-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Acoustic Enrichment Promotes Recovery from Developmentally Degraded Auditory Cortical Processing

Abstract: It has previously been shown that environmental enrichment can enhance structural plasticity in the brain and thereby improve cognitive and behavioral function. In this study, we reared developmentally noise-exposed rats in an acoustic-enriched environment for ϳ4 weeks to investigate whether or not enrichment could restore developmentally degraded behavioral and neuronal processing of sound frequency. We found that noise-exposed rats had significantly elevated sound frequency discrimination thresholds compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 85 publications
5
43
0
Order By: Relevance
“…2). This is consistent with evidence from animal models that environmental deprivation constrains nervous system development; environmental enrichment, however, reverses this maladaptive plasticity [66], reinforcing the concept of auditory learning as a double-edged sword. This hypothesis also aligns with evidence that task reward structure shapes not only whether plasticity occurs, but how it manifests [67, 68].…”
Section: Reward (Limbic) Influences On Auditory Processingsupporting
confidence: 87%
“…2). This is consistent with evidence from animal models that environmental deprivation constrains nervous system development; environmental enrichment, however, reverses this maladaptive plasticity [66], reinforcing the concept of auditory learning as a double-edged sword. This hypothesis also aligns with evidence that task reward structure shapes not only whether plasticity occurs, but how it manifests [67, 68].…”
Section: Reward (Limbic) Influences On Auditory Processingsupporting
confidence: 87%
“…Changes in cortical response selectivity and reliability in the dimensions of time and frequency have been argued to underlie the neurological encoding of the details of acoustic inputs and to account for the limits of auditory perceptual abilities (18,19). We therefore primarily focused on documenting temporal and spectral processing by neurons in the cortical field A1 in our investigation of the neural basis for these sustained, training-induced behavioral changes, while recognizing that any cortical changes that we might record were likely also contributed to by subcortical differences.…”
Section: Resultsmentioning
confidence: 99%
“…We documented in this study the physical and functional impacts of early training at the level of cortical field A1, because it has been compellingly argued that spectro-temporal changes in response selectivity and reliability at this system level most directly account for auditory training-driven changes in perceptual abilities (18,19,(45)(46)(47). It should be noted that both animal and human studies have shown that subcortical plasticity, here undocumented, contributes to cortically expressed changes in temporal and spectral processing driven by this and related forms of intensive auditory training (7,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…The degraded auditory temporal resolution induced by early noise exposure might be related to the changes in the components of excitatory and inhibitory receptor subunits in the auditory cortex. Previous studies in the auditory cortex have shown that early noise rearing induces an increase in NR2B protein expression (Sun et al ., ) or a decreased NR2A/NR2B ratio (Zhu et al ., ), a decrease in GABA A receptor α1 and β3 subunit expression, an increase in GABA A receptor α3 subunit expression, and a decrease in glutamate receptor 2 subunit expression (Xu et al ., ,b), as compared with age‐matched controls. These results indicated that the expression levels of some subunits of GABA A , AMPA and N ‐methyl‐ d ‐aspartate receptors in the auditory cortex determined in adulthood remained at the immature level, owing to early noise rearing.…”
Section: Discussionmentioning
confidence: 99%
“…auditory stimuli, visual stimuli, motor, and social interaction) in the EE. This is consistent with a recent study (Zhu et al ., ) showing that EE promotes the recovery of the auditory cortex from degraded frequency processing by a combination of the effects of the EE components. The finding that EE was more effective in restoring noise‐induced temporal processing deficits than tone exposure environment could be explained by the following.…”
Section: Discussionmentioning
confidence: 99%